Hubungan Antara Kesadaran Diri Dengan Kedisiplinan Belajar Warga Belajar Pada Program Kesetaraan Paket C Di PKBM Farilla Ilmi Kota Padang - Febrianto, Ringga Febrianto; Aini, Wirdatul (Universitas Negeri Padang, 2025)
This study aims to investigate the self-awareness and discipline of learners in the Package C program at PKBM Farilla Ilmi, Padang City, and explore the relationship between these two variables, in response to concerns about low self-awareness among learners, potentially linked to discipline issues. This study employed a quantitative correlational design, sampling 33 respondents from 48 Package C learners at PKBM Farilla Ilmi, Padang City, using stratified random sampling, questionnaires, and statistical analysis (percentage formulas and product moment correlation. The study reveals three key findings: (1) Package C learners at PKBM Farilla Ilmi demonstrate high self-awareness, marked by emotional intelligence, self-assessment, and confidence. (2) They also exhibit excellent learning discipline, reflected in attendance, participation, and assignment completion. (3) A significant positive correlation exists between self-awareness and learning discipline among these learners.